Assessment of the variability of loess soil moisture in pear orchards in different use zones - Skowera, Barbara; Zuśka, Zbigniew; Ziernicka-Wojtaszek, Agnieszka; Ryczek, Marek; Błaszczyk, Jan; Ząbczyński, Mariusz; Baranowska, Alicja J. (Journal of Water and Land Development, 2026)
Soil moisture is one of the most important factors determining crop development, growth and yield. Moisture variability is primarily related to the precipitation, soil texture and vegetation cover. The aim of the study was to assess the impact of soil maintenance systems on moisture content in brown soil formed from loess. The study was conducted during the summer season in 2019–2021 at the Fruit Growing Experimental Station in Garlica Murowana near Krakow operating as part of the Faculty of Biotechnology and Horticulture of the University of Agriculture in Krakow. Soil moisture content was measured at two measuring points in a pear orchard (under the tree crowns and between the rows of trees) and one at the agrometeorological station located next to the orchard. The results showed that the topsoil (0–20 cm) was most susceptible to meteorological conditions. The impact of the soil surface maintenance system in the orchard determined the soil moisture content. The greater the coverage of the soil surface by tree crowns, the higher the moisture content in the soil and the smaller the differences in the soil profile. The key role of soil retention associated with granulometric composition, consisting silt loam, has been confirmed as well as.